Porokeratosis Masquerading As Lupus Vulgaris - Das Sudip; Banerjee Gautam (Wolters Kluwer Medknow Publications, 2004)
Porokeratosis is a specific disorder of kerstinization characterized histologically by cornoid lamella. Lesions of porokeratosis present varied features, often mimicking other dermatological disorders. Herein, we report a case of porokeratosis of Mibelli presenting with verrucous lesions simulating lupus vulgaris.